2004
DOI: 10.1111/j.0022-2445.2004.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in conjugal life in Canada: Is cohabitation progressively replacing marriage?

Abstract: This article aims first to contrast the trends of marriage and cohabitation across different regions in Canada, and second, to assess whether cohabitation constitutes a new stage in the progression to marriage, or an alternative to marriage altogether. Based on various empirical demographic indicators, the analysis shows profound differences across the country. In Quebec, cohabiting unions are now widely accepted as forming the basis for family life, whereas they still largely constitute a childless prelude to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 23 publications
4
98
1
4
Order By: Relevance
“…Early research investigated whether unmarried cohabitation was a prelude to marriage or an alternative to marriage, without providing a defi nitive answer (Lapierre-Adamcyk et al 1987 ;Lapierre-Adamcyk 1989 ). Several years later, it had become clear that, at least in Quebec, unmarried cohabitation was not just premarital cohabitation (Le Bourdais and Marcil-Gratton 1996 ;Le Bourdais and Neill 1998 ;Le Bourdais et al 2000 ;Le Bourdais and Lapierre-Adamcyk 2004 ). Comparative research showed that unmarried couples stayed together longer in Quebec than in Ontario, and were less prone to marry (Le Bourdais and Marcil-Gratton 1996 ;Lapierre-Adamcyk et al 1999 ).…”
Section: Previous Researchmentioning
confidence: 99%
“…Early research investigated whether unmarried cohabitation was a prelude to marriage or an alternative to marriage, without providing a defi nitive answer (Lapierre-Adamcyk et al 1987 ;Lapierre-Adamcyk 1989 ). Several years later, it had become clear that, at least in Quebec, unmarried cohabitation was not just premarital cohabitation (Le Bourdais and Marcil-Gratton 1996 ;Le Bourdais and Neill 1998 ;Le Bourdais et al 2000 ;Le Bourdais and Lapierre-Adamcyk 2004 ). Comparative research showed that unmarried couples stayed together longer in Quebec than in Ontario, and were less prone to marry (Le Bourdais and Marcil-Gratton 1996 ;Lapierre-Adamcyk et al 1999 ).…”
Section: Previous Researchmentioning
confidence: 99%
“…Although the US and Canada are seldom compared to Latin American countries, in light of existing evidence, levels of cohabitation are remarkably lower in the US but not in Canada. The Quebec region has historically had higher levels of cohabitation than the rest of Canada (Le Bourdais and Lapierre-Adamcyk 2004 ;Laplante 2006 ).…”
Section: The Motivation For a Mapmentioning
confidence: 99%
“…Par ailleurs, alors qu'il était quasi obligatoire pour les individus désirant vivre en couple au sortir de la Deuxième Guerre mondiale, le mariage est devenu optionnel à la suite d'une transformation profonde des valeurs, dorénavant orientées vers la poursuite d'un épanouissement personnel plutôt que dictées par un système contraignant de normes et d'obligations (Giddens, 1992 ;Lestheaghe, 1995). L'union libre, encore peu répandue en 1981, s'est imposée progressivement, d'abord comme mode d'entrée en première union ou de remise en couple après l'échec d'un mariage, puis comme cadre de constitution des familles, et ce, plus particulièrement au Québec (Le Bourdais et Lapierre-Adamcyk, 2004). En 2006, les conjoints de fait représentaient 18 % de l'ensemble des couples canadiens et 35 % des couples au Québec (Milan, Vézina et Wells, 2007).…”
Section: Changements Démographiques Et Trajectoires Fami-lialesunclassified